2011
DOI: 10.1051/0004-6361/201016293
|View full text |Cite
|
Sign up to set email alerts
|

A likely exoplanet orbiting the oscillating K-giantαArietis

Abstract: Aims. To search for extrasolar planets around intermediate-mass stars, we are conducting a precise RV survey around K-giants. Methods. We present high-accuracy RV measurements of α Ari made from November 2003 to February 2010. This star belongs to our sample of 55 K-giants studied for extrasolar planet and pulsation searches using the fiber-fed Bohyunsan Observatory Echelle Spectrograph (BOES) attached to the 1.8-m telescope at Bohyunsan Optical Astronomy Observatory (BOAO) in Korea.Results. We find a planetar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Several stars with planetary-mass companions have already been discovered, mainly around red giants (Niedzielski et al 2007(Niedzielski et al , 2009aGettel et al 2012b,a). These findings supplement the slowly growing population of ∼50 planets currently known around evolved stars, discovered in such projects as the McDonald Observatory Planet Search , the Okayama Planet Search (Sato et al 2003), the Tautenburg Planet Search (Hatzes et al 2005), the Lick K-giant Survey (Frink et al 2002), the ESO FEROS planet search (Setiawan et al 2003a,b), the Retired A Stars and Their Companions (Johnson et al 2007), the CORALIE and HARPS search (Lovis & Mayor 2007), and the Boyunsen Planet Search (Lee et al 2011).…”
Section: Introductionmentioning
confidence: 90%
“…Several stars with planetary-mass companions have already been discovered, mainly around red giants (Niedzielski et al 2007(Niedzielski et al , 2009aGettel et al 2012b,a). These findings supplement the slowly growing population of ∼50 planets currently known around evolved stars, discovered in such projects as the McDonald Observatory Planet Search , the Okayama Planet Search (Sato et al 2003), the Tautenburg Planet Search (Hatzes et al 2005), the Lick K-giant Survey (Frink et al 2002), the ESO FEROS planet search (Setiawan et al 2003a,b), the Retired A Stars and Their Companions (Johnson et al 2007), the CORALIE and HARPS search (Lovis & Mayor 2007), and the Boyunsen Planet Search (Lee et al 2011).…”
Section: Introductionmentioning
confidence: 90%
“…The RV standard star τ Ceti shows an rms scatter of 6.7 m s −1 over the time span of our observations and demonstrates the long-term stability of the BOES (Lee et al 2011). …”
Section: Observations and Analysismentioning
confidence: 92%
“…We have reported two new exoplanets (Han et al 2010;Lee et al 2011) and confirmed an exoplanet ) and an oscillating star (Kim et al 2006).…”
Section: Observations and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Each estimated S/N at an I 2 region was about 200 with a typical exposure time ranging from 10 to 20 min. The long-term stability of the BOES was demonstrated by observing the RV standard star τ Ceti, which was constant with an rms scatter of 6.8 m s −1 over the time span of our observations (Lee et al 2011(Lee et al , 2012. We obtained 24 and 32 spectra each for HD 208527 and HD 220074, respectively, from September 2008 to June 2012.…”
Section: Observations and Reductionmentioning
confidence: 99%